HUMAN ERROR STILL CAUSES A THREAT TO CONSTRUCTION INDUSTRY: IS IT BECAUSE OF NEGLIGENCE OR LACK OF KNOWLEDGE? (Evidence from the construction industry of Tashkent City, Uzbekistan) - Zikriyoev, Aziz; Nurimbetov, Ravshan (International Journal of Psychosocial Rehabilitation, 2020)
Current research presents a systematic analyses based on approach for Prospective Health and Safety Performance on construction sites, with causal relationships and interactions between international standards and Uzbek construction site regulations taken into account. Four typical types of construction enterprises, namely the private enterprise, state enterprise, joint enterprise, and international enterprise are selected as sample to measure the level of safety performance given variables. Results provide professional safety performance practice in the construction site, and indicate tha the level o total knowledge and practice of construction site personals. It can be explained that the construction sites hav graduall matured with the international norms, and conventions for improving risk assessment low level of accident rate in construction industry. Health and Safety performance differences existing due to organizational structure and skilled employee of the construction company categories are compared and analyzed based on evaluation results. This article provides insights into conceptual relationships among Health and Safety performance variables and goals, which can facilitate the development of ILO 155 and 167 conventions in construction industry of Uzbekistan. Main purpose of the current paper is examine risk level on site, evaluate human factor and preventing accident rate by reducing workers knowledge and experience for self-awareness.